IDENTIFIKASI KESESUAIAN LAHAN UNTUK JATI (Tectona grandis Linn.f) DI PT. MELAPI TIMBER, KALIMANTAN TIMUR Identify Suitable Land for Jati (Tectona grandis L.f) in PT. Melapi Timber, East Kalimantan - Susanti .; Prijanto Pamoengkas; Cahyo Wibowo (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2018)
Land evaluation of a tract of land, for its suitability to be planted with a particular plantation species is an importantstep for species choice in plantation forest. A weight factor matching (WFM) approach of this study, was used to identifysuitable land for jati (Tectona grandis L.f) in PT. Melapi Timber, East Kalimantan. Land suitability is affected by climate,soil and topograph. According to WFM, the results indicated that important variables which limit T. grandis in theresearch area were pH, cation exchange capacity (CEC), potassium (P) and soil depth condition. The study results showthat 4 of 5 land units are marginally suitable (S3) for T. grandis cultivation in PT. Melapi Timber.Key words: Land evaluation, suitability, Tectona grandis L.f., weight factor matching (WFM)